Triggering factors in sensitive skin from the worldwide patients' point of view: a systematic literature review and meta‐analysis. (24th October 2019) - Brenaut, E.; Barnetche, T.; Le Gall‐Ianotto, C.; Roudot, A.‐C.; Misery, L.; Ficheux, A.‐S.
Abstract: Sensitive skin (SS) is a syndrome defined by the occurrence of unpleasant sensations in response to stimuli that normally should not provoke such sensations. In most patients, symptoms occur within 1 h following exposure to trigger factors and may persist for minutes or even hours. Numerous triggering factors (physical, chemical or psychological) are suspected and described in articles. The aim of this article was to perform a systematic literature review to collect data on the triggering factors involved in SS and to then perform a meta‐analysis. Thirteen studies were included in the systematic literature review. Subjects were classified into groups, SS or no sensitive skin (NSS), and triggering factors were researched through responses to different questions. SS could be triggered by numerous factors. The most important triggering factor was cosmetics, with an odds ratio (OR) equal to 7.12 [3.98–12.72]. Other triggering factors were physical (variations in temperature, cold, heat, wind, sun, air conditioning, wet air and dry air), chemical (water and pollution) or psychological (emotional) factors. After cosmetics, the most important factors were wet air, OR 3.83 [2.48–5.91]; air conditioning, OR 3.60 [2.11–6.14]; heat, OR 3.5 [2.69–4.63]; and water, OR 3.46 [2.56–4.77].